CHARACTERISTICS OF ACHIEVING EFFICIENCY IN THE EDUCATION PROCESS BASED ON THE INNOVATION APPROACH - Safiya NIYOZOVA (Scholar Express Journal, 2024)
This article provides detailed information on the use of an innovative approach to achieve efficiency in the educational process. By strengthening its shortcomings with new technologies, the overall efficiency of the educational system can be increased. Such an approach views innovation not as a manufactured "external" measure, but as a deeply meaningful demand and system knowledge, deliberate restructuring
Keywords: innovation; education; training; process